REVEALING THE FACES OF RURAL POVERTY IN INDONESIA: A CASE FROM TEMANGGUNG, CENTRAL JAVA - Rofah Rofah; Astri Hanjarwati; Jamil Suprihatiningrum (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Previous research on poverty in rural areas of Indonesia has identified structural poverty as a significant underlying cause. The objective of this article is to provide an overview of the internal and external factors contributing to poverty in rural Java. The study utilized quantitative research methods and was conducted in the Merah Village, Temanggung, Central Java, which was selected as a representative area falling within the national poverty threshold. The findings indicated that rural communities were confronted not only with structural poverty issues such as limited access to economic resources, education, and empowerment. In addition, cultural poverty further compounded the issue, as it was characterized by pervasive perceptions of subjective well-being among the rural communities, with a majority (81.7%) feeling poor and uncertain about finding a way out of their situation, while only a minority (18.3%) felt prosperous. The prevalent perception of cultural poverty is closely intertwined with the structural characteristics of Javanese society, particularly the concept of 'nerimo', which can be interpreted as the belief that poverty is a God-given destiny that cannot be rejected or altered.Berbagai studi terdahulu tentang kemiskinan pedesaan di Indonesia telah mengungkapkan kemiskinan struktural telah menjadi penyebab utama. Artikel ini bermakud untuk mendeskripsikan penyebab internal dan eksternal kemiskinan di pedesaan Jawa. Penelitian dilakukan dengan menggunakan metode kuantitatif, dengan mengambil lokasi di Desa Merah, Temanggung, Jawa Tengah sebagai representasi dari wilayah yang masih berada dalam garis kemiskinan nasional. Hasil penelitian menunjukkan bahwa masyarakat pedesaan tidak hanya dihadapkan pada problem kemiskinan struktural seperti misalnya minimnya akses ke sumber-sumber ekonomi, pendidikan, dan pemberdayaan. Namun juga semakin diperparah dengan kemiskinan kultural yang ditandai dengan kuatnya persepsi terhadap kesejahteraan subyektif, seperti misalnya perasaan bahwa mereka adalah orang miskin dan kebingungan bagaimana mencari jalan keluar atas situasi tersebut (81,7%), selebihnya hanya 18,3% yang merasa sejahtera. Kuatnya persepsi kemiskinan kultural ini berkaitan erat dengan karakter struktur masyarakat Jawa yang ‘nerimo’, yang dapat diartikan sebagai keyakinan bahwa kemiskinan mereka adalah takdir tuhan yang tidak bisa ditolak.